A Phonological Analysis of English Loanwords Inflected With Arabic Morphemes in Urban Jordanian Spoken Arabic - Aseel Zibin (SAGE Open, 2019)
This article tackles a phenomenon in Urban Jordanian Arabic (UJA) where young individuals (mainly females) in Amman, the capital of Jordan, add the Arabic suffix - ɪk , which is glossed as second female singular or as a possessive pronoun, to English loanwords to sound more “modern,” for example, “I love you” becomes [lʌvvɪk]. Through examining the data, two initial hypotheses were formalized, namely, when the Arabic suffix - ɪk is added to English monosyllabic words which have a short vowel in the nucleus (e.g., love), the coda is geminated. However, if the word is disyllabic (e.g., mobile) or monosyllabic, but has a long vowel (e.g., juice) or a diphthong (e.g., face) in the nucleus, no gemination occurs. This article analyzes this phenomenon based on hierarchical syllable structure, metrical phonology, and optimality theory.